Targeted drug monitoring in oncology for personalized treatment with use of next generation analytics - Wei Li; Chaoling Wen; Bin Ye; Pranjal Gujarathi; Meghraj Suryawanshi; Kuldeep Vinchurkar; Imtiyaz Bagban; Sudarshan Singh; Opeyemi Joshua Olatunji (Discover Oncology)
Abstract Therapeutic drug monitoring (TDM) is a clinical procedure aimed at maintaining plasma drug concentrations within a specific therapeutic range, thereby maximizing the safety and efficacy of pharmacological therapy. Conventional oncology strategies face challenges like non-specific toxicity, drug resistance, incomplete tumor eradication, high costs, and significant side effects that impact quality of life. Moreover, conventional therapy offers limited benefits in advanced stages, pose risks of secondary cancers and immune suppression, and lack personalization, highlighting the need for targeted, innovative approaches. In modern oncology, TDM has gained significant interest due to narrow therapeutic windows, significant inter-individual variability in pharmacokinetics, and the complexity of cancer pharmacotherapy. This study reviews the role of TDM in oncology with more emphasis on pharmacogenetic testing, immunoassays, and liquid-chromatography-mass spectroscopy (LC-MS/MS) techniques, highlighting its applications in optimizing the dose during immunotherapies, targeted therapies, and chemotherapeutics. Moreover, the review discusses the challenges and limitations associated with TDM in oncology, such as the requirement of robust clinical evidence, standardized practices, and integration with personalized medicine approaches. Emerging technologies, including AI and machine learning, are also considered for their potential to enhance TDM in oncology. Graphical abstract